2003
DOI: 10.1038/sj.bdj.4809941
|View full text |Cite
|
Sign up to set email alerts
|

Infratemporal and submasseteric infection following extraction of a non-infected maxillary third molar

Abstract: A case is described where an otherwise fit young female patient developed a large submasseteric abscess following the uneventful extraction of a non-infected maxillary third molar under local anaesthesia with intravenous sedation. This report highlights the difficulty of clinical diagnosis especially in the early stages of the infection. This case also demonstrates the imaging modalities used to confirm the diagnosis. It is likely that the infection in this case arose in an infratemporal fossa haematoma result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…8 Gallagher et al and Diacono et al reported trigeminal neuralgia and paraesthesia as additional presentation due to involvement of maxillary and mandibular branches of the trigeminal nerve, which was not seen in our case. 9,10 When swelling is extending to superficial temporal space from infratemporal space it gives an hourglass appearance of the face which is mainly due to the tight connection of the temporal fascia to the zygomatic arch which was seen in our case. 2 Bratton et al stated that in all head and neck space infections, CT is standard than MRI for diagnosing them, CT has correctly diagnosed masticator abscess in all 30 patients.…”
Section: Discussionsupporting
confidence: 50%
“…8 Gallagher et al and Diacono et al reported trigeminal neuralgia and paraesthesia as additional presentation due to involvement of maxillary and mandibular branches of the trigeminal nerve, which was not seen in our case. 9,10 When swelling is extending to superficial temporal space from infratemporal space it gives an hourglass appearance of the face which is mainly due to the tight connection of the temporal fascia to the zygomatic arch which was seen in our case. 2 Bratton et al stated that in all head and neck space infections, CT is standard than MRI for diagnosing them, CT has correctly diagnosed masticator abscess in all 30 patients.…”
Section: Discussionsupporting
confidence: 50%
“…A previous dental or sinus infection, as well as fracture of the sinus wall, are also among the most frequent causes of this infection. Gallagher and Marley ( 5 ) have also reported an infratemporal fossa infection following the extraction of an uninfected maxillary third molar, and they also have related this condition to the hematoma of the pterygoid plexus. It is not possible to determine whether the tooth in our case had been infected prior to extraction.…”
Section: Discussionmentioning
confidence: 98%
“…Infection of the infratemporal space is a rare clinical condition which occurs mostly due to dental infection, tooth extraction, fractures involving the maxillary sinus and infections of the maxillary sinus. Generally, the cause is the fracture of the maxillary antrum or the infection of a maxillary molar tooth ( 4 , 5 , 6 , 7 , 8 ).With regard to the proximity to some important anatomical areas of the head, dealing with infratemporal space infection needs great consideration both in examination and surgical practice ( 1 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 We therefore recommend pre-and postoperative administration of antibacterial agents for RA patients undergoing tooth extraction. 5 Early diagnosis of abscess development is important, as is the maintenance of good oral hygiene, for example by gargling with disinfectants.…”
Section: Discussionmentioning
confidence: 99%